Influence of borate structure on the thermal stability of boron-containing phenolic resins: A DFT study. (September 2015) - Bian, Cheng; Wang, Yong; Wang, Shujuan; Zhong, Yuhu; Liu, Yun; Jing, Xinli
Abstract: In the present study, the density functional theory (DFT) was applied to investigate the influence of borate structure on the thermal stability of phenolic resin modified by boric acid (BPR) and phenylboronic acid (PBPR). The bond dissociation energy (BDE) and electronic structure, which represent the stability of chemical bonds and reactivity of functional groups respectively, were obtained with the BPW91, B3LYP, CAM-B3LYP and M06-2X method based on simplified models of BPR and PBPR. The BDE of B–O bond was higher than C–O and C–C bonds, which may contribute to the thermal stability of the resins. Moreover, the population analysis indicated that the formed borate structures from boric hydroxyls and phenolic hydroxyls could inhibit the active sites, such as phenolic hydroxyls and methylenes in PR. The inhibiting effect worked well in both BPR and PBPR, especially in the structures with eight-membered heterocycles formed by the borate and methylene bridges. These results provide useful clues for understanding the roles of borate structure in improving the thermal stability of PR, which are of practical importance in the design and optimization of thermal stable resins.